2016
DOI: 10.3892/ol.2016.4133
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tumor necrosis factor-α-induced protein 8 in stage III gastric cancer and the correlation with DcR3 and ERK1/2

Abstract: Abstract. Tumor necrosis factor (TNF)-α-induced protein 8 (TIPE) is a recently identified protein that is considered to be associated with various malignancies, including esophageal, breast and pancreatic cancer; however, the importance of TIPE in gastric cancer (GC) remains unknown. Decoy receptor 3 (DcR3) is a member of the tumor necrosis factor receptor superfamily that is expressed in digestive system neoplasms. The expression of DcR3 is regulated by the mitogen-activated protein kinase (MAPK)/MAPK kinase/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Edfeldt et al 23 found that TNFRSF6B is related to poor survival and can be considered as a marker for liver metastases. Hu et al 24 showed that the expression of DcR3 is higher in the tumor tissues of GC than in paracarcinoma tissues and that TNFRSF6B is important in assessing the stage of GC. Currently, studies on TNFRSF6B polymorphisms are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Edfeldt et al 23 found that TNFRSF6B is related to poor survival and can be considered as a marker for liver metastases. Hu et al 24 showed that the expression of DcR3 is higher in the tumor tissues of GC than in paracarcinoma tissues and that TNFRSF6B is important in assessing the stage of GC. Currently, studies on TNFRSF6B polymorphisms are rare.…”
Section: Discussionmentioning
confidence: 99%
“…As prolonged JNK phosphorylation uncouples MEK-mediated ERK activation in a c-Jun-dependent manner (29), opposing effects of ERK and JNK-p38 MAPKs on apoptosis have been found in nerve growth factor withdrawal cells (30). Meanwhile, TIPE expression was found to be positively correlated with ERK1 but not ERK2 as documented in gastric cancer (31). Hence, the exact function of MEK phosphorylation in TIPE-mediated promotion of tumor formation remains unclear and needs further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of DcR3 is regulated by the mitogen-activated protein kinase (MAPK)/MAPK kinase/extracellular signal-regulated kinase (ERK) signaling pathway. The expression of TNFA-induced protein 8, ERK1/2 and DcR3 in the tumor tissues of GC was significantly increased compared with paracarcinoma tissues and TNFA-induced protein 8 expression positively correlated with DcR3 and ERK1/2 levels, which may be involved in the cell apoptosis of gastric and pancreatic cancer [55,56].…”
Section: Tumor Necrosis Factor-related Decoy Receptorsmentioning
confidence: 92%
“…These fibroblasts interact with collagen matrix, and aberrantly activated Akt increases DcR3 expression and protects these cells from the FasL-dependent apoptotic pathway. TNFRSF6B is also induced by TNFA-induced protein 8, a recently identified protein that is considered to be associated with various malignancies, including esophageal, breast, gastric, and pancreatic cancer [55]. The expression of DcR3 is regulated by the mitogen-activated protein kinase (MAPK)/MAPK kinase/extracellular signal-regulated kinase (ERK) signaling pathway.…”
Section: Tumor Necrosis Factor-related Decoy Receptorsmentioning
confidence: 99%